An Assessment of the Impact of Business Plan Competitions on Enterprise Development in Kenya: A Case Study of Chora Bizna Enablish LaunchPad - Mboha, Sylvance (European Scientific Journal, ESJ, 2018)
The purpose of the study was to establish the impact of business plan competitions (BPCs) on enterprise development as measured by number of new ventures created and sustained, number and value of jobs created, revenue turnover growth and value of assets. The BPC was dubbed â€œChora Bizna Enablis LaunchPadâ€. The study used a quasi-experimental design. The target population was the top 100 national finalists who undertook a one week intensive training at Multimedia University. The accessible population was 52 finalists, of which 45 successfully responded. This number was used as the test group. A matched sample of non-participants was drawn from small business owners in Nairobi County. Data was analysed using SPSS. The results revealed that out of the 45 national finalists interviewed, 35 went ahead to implement their business plans, creating employment for 210 people who earned a total monthly salary of over 4 million Kenya shillings. Their enterprises were posting an aggregate of 13.8 million Kenya shillings in revenue every month, and the entrepreneurs reported an accumulated value of assets estimated at a total of 518 million Kenya shillings. On average, each participant in the BPC employed more than twice the number of employees reported by non-participants and disbursed nearly double the average total monthly salaries reported by non-participants. Similarly, the average revenue of BPC participants quadrupled that of non-participants. BPC participants also reported significantly higher average value of accumulated assets compared to non-participants. Therefore, such competitions are effective for fostering enterprise development and more should be held.